2012
DOI: 10.1242/jeb.063941
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation pattern depends on the strategy chosen by zebra finches to solve an orientation task

Abstract: SUMMARYZebra finches (Taeniopygia guttata) were trained to find food in one of four feeders on the floor of an aviary. This feeder was always in the same place during training and was additionally marked by a distinct pattern. In the test trial the distinctly patterned feeder was interchanged with one of the other feeders, so that the birds had to decide to use either the pattern or the original location for finding food. Half of the birds used one strategy and half used the other. According to the strategy ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…Similarly, in zebra finches, the lateral nido-mesopallium shows more IEG activation in males after a first exposure to a female (Lieshoff et al, 2004;Bischof, 2002, 2006) and also after orienting based on visual textual cues (Mayer and Bischof, 2012). The two areas investigated in pigeons and zebra finches receive inputs from entopallium Wild, 2004, 2005;Sadananda and Bischof, 2006;Sadananda et al, 2007) and might be comparable in the two species (Shimizu et al, 2010).…”
Section: The Visual System Of Birdsmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, in zebra finches, the lateral nido-mesopallium shows more IEG activation in males after a first exposure to a female (Lieshoff et al, 2004;Bischof, 2002, 2006) and also after orienting based on visual textual cues (Mayer and Bischof, 2012). The two areas investigated in pigeons and zebra finches receive inputs from entopallium Wild, 2004, 2005;Sadananda and Bischof, 2006;Sadananda et al, 2007) and might be comparable in the two species (Shimizu et al, 2010).…”
Section: The Visual System Of Birdsmentioning
confidence: 85%
“…Aiming to determine which regions of the chick brain undergo plastic changes, Egorova and Anokhin (2003) measured neuronal activity-dependent immediate early gene expression (cfos) of chicks after priming in a running wheel or acoustical stimulation and compared them with the unstimulated controls. Immediate early genes are supposed to play an important role in neuronal plasticity related to learning (Guzowski, 2002;Jones et al, 2001;Kubik et al, 2007;Lanahan and Worley, 1998) and have been successfully used to stain neuronal activity in mammals as well as in birds (Cole et al, 1989;Mayer and Bischof, 2012;Mayer et al, 2010;Mello et al, 1992;Milbrandt, 1987;Smulders and DeVoogd, 2000). By focusing on the brain areas that have been activated by both kinds of non-visual activating experiences, Egorova and Anokhin intended to find the areas involved in emergence of predispositions.…”
Section: Processing Of Innate Predispositions In Birdsmentioning
confidence: 99%
“…In zebra finches, HP IEG expression is enhanced in learning and memory tasks requiring use of spatial cues (Mayer & Bischof, 2012). Interestingly, we found that expression was greater during “middle-age” in the HP of females compared to males.…”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps surprising because in mammals [e.g. Packard et al, 1989] and birds [Mayer and Bischof, 2012; see also Shimizu et al, 2004] such guidance strategies typically recruit the Str or some other telencephalic structure. In this context, we were therefore not surprised by the trend of greater activation in the Str in the Geometry-Feature group.…”
Section: Discussionmentioning
confidence: 99%
“…The data from the DP are less easy to interpret, but here general visual processing may be relevant. We therefore hypothesize that the LP, and to a lesser extent the DP, region in the terrestrial toad R. arenarum is in some way involved in spatial guidance by visual cues resembling the telencephalic-tectofugal activation in zebra finches (Taeniopygia guttata) associated with locating a goal by visual features [Mayer and Bischof, 2012].…”
Section: Discussionmentioning
confidence: 99%